Regional development in Lithuania considering multiple objectives by the MOORA method - Brauers, Willem Karel M.; Ginevičius, Romualdas; Podvezko, Valentinas (Technological and Economic Development of Economy, 2010)
The inequality between the regional incomes in a nation with a developed fiscal and parafiscal regime including social security will be equilibrated automatically by transfer payments from the richer to the poorer regions. The automatic system is not a guaranty for success. Internationally a project oriented system of the international organizations is known instead of an automatic system but the final goal is not always very clear. Multiple Objectives Optimization looks more robust to obtain regional and international development. Moreover a system of transfer payments is not sufficient to measure the well being of a regional population. In the well‐being economy, each individual would have to feel good concerning material wealth, health, education, all kind of security and concerning the environment. With other words, multiple objectives have to be fulfilled. However, these different multiple objectives are expressed in different units. Weights are most of the time used to equalize these different units. Introduction of weights means introduction of subjectivity. In order to avoid this dilemma, the internal mechanical solution of a ratio system, producing dimensionless numbers, is preferred: MOORA. In addition, this outcome creates the opportunity to use an additional non‐subjective reference point theory. The choice and importance of the objectives is also non‐subjective if all stakeholders involved come to an agreement. This theory is applied on the different counties of Lithuania. At that moment it is no more only a question of redistribution of income but also of a national policy of new constructions, of tourism development, of pollution abatement and of energy renewables, after the European Commission “related to the promotion of local employment”.Article in English.Lietuvos regioninės plėtros daugiaaspektis vertinimas MOORA metoduSantrauka. Nelygybė tarp skirtingų regionų pajamų išlyginama remiant skurdesnius regionus, t. y. dali turtingesnių regionų pajamų pervedant skurdesniems. Tačiau tokia sistema nėra sėkmės garantas, be to, ji nepajėgi įvertinti regiono gyventojų geroves. Plačiai žinoma tikslinės paramos sistema, kurią taiko tarptautines organizacijos, tačiau jos galutiniai rezultatai ne visada būna akivaizdūs. Esant gerovės ekonomikai, kiekvienas individas turėtų būti patenkintas materialine gerove, sveikatos apsauga, švietimu, saugumu bei aplinkosauga. Kitaip tariant, turi būti išpildyti daugelis siekių. Tačiau šie skirtingi siekiai išreiškiami skirtingais mato vienetais. Be to, skirtingiems siekiams sulyginti pasitelkiami reikšmingumui, kurie suteikia subjektyvumo. Siekiant to išvengti, pirmenybė teikiama reitingavimo sistema turinčiam MOORA metodui, paverčiančiam domesinius skaičius beįdomesniais. Be to, jis sukuria galimybę naudoti nesubjektyvią ekstrinio taško teoriją. Tikslai ir jų svarba yra objektyvūs, jei visos suinteresuotos puses dėl jų sutaria. Ši teorija pritaikyta vertinant daugelį Lietuvos apskričių. Šiuo metu svarbu ne tik perskirstyti regionu pajamas, bet ir formuoti naujų statybų, turizmo vystymo, taršos mažinimo, atsinaujinančiosios energetikos nacionalinę politiką pagal Europos Komisijos programą “Vietinio užimtumo skatinimas”.Reikšminiai žodžiai: MOORA, proporcinė sistema, ekstreminio taško teorija, regioninis vystymasis, pajamų perskirstymas, darbo jėgos nutekėjimas.First published online: 10 Feb 2011